Planejamento por cenário nas tomadas de decisão estratégica: avaliação da efetividade de estudos prospectivos nas organizações - Kobayashi, Clarice Miyaco Okano (2023)
At a global level, within the various initiatives, strategic plans based on future studies permeate organizations, non-governmental entities, and countries. It is known that conducting a strategic planning project based on scenarios requires investments, there are several actors involved, it is difficult to maintain actions in accordance with the dynamism and complexity of environments and these can affect the credibility of the methods used. Therefore, organizations need to understand that positive outcomes and risks can be the result of these investments. This study aims to comprehend the use of scenario planning through empirical research with data collection, regarding the nature of its process as well as its effectiveness in organizational performance. Decision-making, whether formal or informal, assists and shapes the future of the corporation in achieving its goals or mitigating potential risks, which can be anticipated through scenario exercises. To ensure effectiveness, because of implemented foresight studies, it is necessary to validate the real applications of scenario creation in the decision-making process of professionals in the strategy field. From the studies, not only can a clear difference be perceived between industries, organizational structures, leaderships, and sectors, but also expands the understanding of the strategic value of using scenario in the same sector where organizational maturity is found in different phases (theory and applied practice).